A match on dry grass : community organizing as a catalyst for school reform - Warren, Mark R., 1955- (Oxford University Press, 2011)
"A Match on Dry Grass argues that community organizing represents a fresh and promising approach to school reform as part of a broader agenda to build power for low-income communities and address the profound social inequalities that affect the education of children."--Provided by publisher.